Grain-size analysis and geochemical data of several event deposits in Lake Iznik (NW Turkey) - Gastineau, Renaldo; Sabatier, Pierre; Fabbri, Stefano C; Anselmetti, Flavio S; Roeser, Patricia A; Findling, Nathaniel; Arnaud, Fabien; Şahin, Mustafa; Gündüz, Serkan; Franz, Sven-Oliver; De Sigoyer, Julia (In: Gastineau, R et al. (2021): Sedimentary and geochemical analyses from 14 sediment cores of Lake Iznik, NW Turkey [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.935167, 2021)
Grain-size analysis can help to discuss the energy of an event deposit and characterize its transport and depositional mechanism. The grain-size distribution at the event-deposit locations was analysed at a 5 mm vertical sampling interval on 7 cores (IZN19-13, IZN19-20, IZN19-21, IZN19-22, IZN19-24, IZN19-27, IZN19-29). A Beckman Coulter Life Science 13 230 XR laser particle-size analyser was used (EDYTEM Laboratory, University Savoie Mont-Blanc) with sonication to avoid particle flocculation. Two runs with a 30 s-long measurement were applied without any pre-treatment. Grain-size parameters were directly extracted from the Adapt software V. 1.3.337 and Gradistat V9.1 (Blott & Pye, 2001; doi:10.1002/esp.261). The sorting index was calculated according to Folk & Ward (1957; doi:10.1306/74D70646-2B21-11D7-8648000102C1865D).
Keywords: grain-size; Grain-size analyses; Iznik; Lake; sediment; sediment core data; Turkey